Ekologiczne aspekty pedagogiki specjalnej Gestalt w kontekście rozwoju dzieci z niepełnosprawnością intelektualną i zaburzeniami ze spektrum autyzmu - Godawa, Szymon (Studia Etnologiczne i Antropologiczne, 2017)
The following article focuses on ecological aspects of Special Pedagogics Gestalt. This is a very important theme concerning working with children with mental disability and ASD. In this article, ecology of sound, ecology of the area, ecology of nutrition are of great importance.